Christan Spirituality high Middle Ages and Reformation - Raitt, Jill (New York The Crossroad Publishing, 1988)
Series of three volumes : v. 1. Origins of the twelfth century ; v. 2. High Middle Ages and Reformation ; v. 3. Post-Reformation and modern. A multivolume series with more than 500 contributing scholars worldwide, presenting the spiritual wisdom of the human race in its historical unfolding, from prehistoric times, through the great religions to the meeting of traditions at the present
Keywords: Spiritual life -- Christianity -- History of doctrines -- Middle Ages, 600-1500. Spiritual life -- Christianity -- History of doctrines -- 16th century. Vie spirituelle -- Christianisme -- Histoire des doctrines -- 600-1500 (Moyen Âge) Vie spirituelle --